2012
DOI: 10.1002/hast.81
|View full text |Cite
|
Sign up to set email alerts
|

Seven Things to Know about Female Genital Surgeries in Africa

Abstract: Female Genital Mutilation is a cultural and historical practice engrained in the African Culture.This practice is part of the African Rite of Passage; where a young girl passes on from being a child into being a grown woman. According to Martha Nussbaums's Capability Approach this practice undermines the woman and violates her rights as a human being, on the other hand Melville Herskovits' Cultural Relativist theory encourages acceptance and respect of the various cultures and their beliefs; thus making female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Although we do not necessarily share a single policy perspective with respect to such practices, nor a uniform moral assessment of every feature of them, we are united in a concern about widespread inaccuracies, inconsistencies, double standards, and Western cultural bias in the prevailing discourses on genital cutting of children. Some of us have evolved in our thinking over the years in response to scholarship illuminating such problems (e.g., Abdulcadir et al 2012;van den Brink and Tigchelaar 2012;Bell 2005;Darby and Svoboda 2007;Davis 2001;DeLaet 2009;Earp 2015;Ehrenreich and Barr 2005;Johnson 2010;Merli 2010;Njambi 2004;Obiora 1996;Onsongo 2017;Svoboda 2013;Tangwa 1999). Together, we argue for a more coherent, sex-and gender-inclusive approach that recognizes (1) the special vulnerability of young…”
Section: Appendix About the Authorsmentioning
confidence: 88%
“…Although we do not necessarily share a single policy perspective with respect to such practices, nor a uniform moral assessment of every feature of them, we are united in a concern about widespread inaccuracies, inconsistencies, double standards, and Western cultural bias in the prevailing discourses on genital cutting of children. Some of us have evolved in our thinking over the years in response to scholarship illuminating such problems (e.g., Abdulcadir et al 2012;van den Brink and Tigchelaar 2012;Bell 2005;Darby and Svoboda 2007;Davis 2001;DeLaet 2009;Earp 2015;Ehrenreich and Barr 2005;Johnson 2010;Merli 2010;Njambi 2004;Obiora 1996;Onsongo 2017;Svoboda 2013;Tangwa 1999). Together, we argue for a more coherent, sex-and gender-inclusive approach that recognizes (1) the special vulnerability of young…”
Section: Appendix About the Authorsmentioning
confidence: 88%
“…It is possible that this care intervention redressed obstetric In the developing world, prolonged second stage of labour, extensive perineal tears, damage to the adjacent structures like the urethra, the bladder, and the rectum, vesicovaginal and rectovaginal fistulae, birth asphyxia, and stillbirth can follow vaginal delivery without defibulation [7]. In contrast, studies from the developed world have shown that a high standard of antenatal care, defibulation, skilled birth attendants, and professional surveillance of labour can minimise the adverse obstetrics outcomes [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…[113] While many circumcised men seem to "have no conscious issue" with being circumcised, it is possible that they have suffered a deep psychological trauma that is repressed within the unconscious psyche [20]. Indeed, many women who have undergone even extreme forms of female genital cutting/FGM report being "satisfied" with their sex lives [160]; however, this may be due in part to the fact that they lack adequate knowledge of the relevant genital anatomy (such as the innervations and functions of the clitoris), and therefore may not know what it is that they are "missing" [121]. A similar phenomenon may occur in the case of circumcised men, who typically know very little about the anatomy and functions of the penile foreskin-for further discussion, see Earp and Darby [123].…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 99%